PERANCANGAN SIMULASI KALKULATOR INDEKS MASA TUBUH BERBASIS ARDUINO UNO DAN SIMULASI WOKWI - Bagaskoro, Christopher; Kuspranoto, Abdul Haris (LPPM POLBITRADA, 2023)
Ideal body weight is everyone's dream. Not only does having a body shape support your appearance, ideal body weight also indicates a healthy body condition. Maintaining body weight is one of the main keys to having a healthy and fit body. To find out whether our weight is ideal, we can see it from the Body Mass Index (BMI) measurement. BMI is measured by comparing height and weight. Basically, BMI is a benchmark that can be used as a way to find out ideal body weight. As time progresses, the use of existing technology is widely applied in the world of health. One of them is a BMI Calculator that uses a microcontroller such as Arduino UNO. BMI Calculator is a measurement tool commonly used to evaluate a person's Body Mass Index (BMI). This tool helps individuals and healthcare professionals to quickly determine whether a person is within a healthy weight range, underweight, or overweight.